The formation of character among students of primary school teacher education in a public higher education institution in Indonesia - Supriyadi Supriyadi; Ika W. Utamining Tias; Amrina Izzatika (Lighthouse Publishing, 2021)
The national education system so far has not been satisfactory. Looking at this situation, several solutions have been proposed, e.g., updated version of curriculum. However, this solution is not adequate because educators are also expected to be able to prepare students' attitudes and behavior so that they can face the demands of the current situation and the dynamics of change that are rapidly developing. Changes that occur are not only in knowledge and technology but also in aspects of moral values in social life. In addition to family as a center of education, a higher education institution environment also requires a function of character education to shape students’ personality be more positive as expected. In other words, the process of character formation and habituation is the responsibility of not only students’ parents within family domain but also formal higher education institutions. With the various problems that exist at higher education level, character building for primary teacher education (henceforth PGSD) students is needed that they are expected to be able to improve and apply their knowledge, study, appreciate and apply character values in their daily life behavior. Therefore, the purpose of this study is to identify PGSD students’ character formation and ensure the results of the character formation process in a higher education institution in Indonesia.